Effect of different concentration of functionalized graphene on charging time reduction in thermal energy storage system. (2021) - Kumar, Pramod; Kumar Singh, Pradeep; Nagar, Sumit; Sharma, Kamal; Saraswat, Manish
Abstract: The experimental work was carried out on the thermal energy storage system to test the thermal performance with the use of carboxyl functionalized Graphene (–COOH) doped with phase change material (Paraffin wax). The volume concentrations were varied from 0.25 to 1% at an increment of 0.25%. The HTF (Heat transfer fluid) which was water had its temperature varied between 80 °C and 90 °C at a 5 °C interval and the flow rate of water (HTF) was kept as 12.5 ml/sec or 50 ml in 4 s. In this experiment charging time reduces with increase of the Graphene concentration in terms of vol%. This research also included measuring nanofluid thermal properties at varying concentration and inlet temperature of HTF. Based on research from the experiments. It is observed that, due to an increase in thermal conductivity, the charge time reduction rate increase by up to 20% to 30% because of variance in the HTF inlet temperature when used with doped PCM material. Better performance metrics such as charging power, greater overall efficiency and increased energy amount are all recorded. When the charging time is reduced by 30% to 50% using the nanomaterial in PCM at 1 vol%, the large amount of energy was stored in the short duration of the time.